Determinación del índice de infestación por Varroa destructor en colonias de Apis mellifera, en condiciones naturales - Polo Corro, José Luis (2022)
The objective of this research was to determine the infestation index by Varroa destructor in colonies of Apis mellifera without control measures, in the province of Santiago de Chuco, La Libertad, Peru; since there are no studies on this subject in the área. For which we proceeded to identify the places where the hives were that did not have any type of control for the various pests, such as varroa, which has implications for the bee population and the products they make such as honey, propolis, royal jelly and wax. To determine the infestation index of Varroa destructor on Apis mellifera , the test described by David De Jong, known as “bee washing”, was used. For which 4 colonies of bees that were in natural conditions were evaluated, determining that colony C-1 had an infestation index of 7.4%, which indicates that it is in a medium intensity, the other colonies C-2, C-3, and C-4 had an infestation index of 3.2%, 3.6% and 2.2% respectively, which means that they have a low intensity; therefore, it is concluded that in bee colonies without any type of control, the varroa infestation rate is higher when it is closer to human populations. In addition, it was determined that the varroa infestation index is inverse to altitude.